Ecofriendly Control for Stored-Product Pest, Oryzaephilus surinamensis (Order: Coleoptera, Family: Silvanidae) - Fatma H. Galal (مجلة بغداد للعلوم)
Dates are considered one of the most important foods consumed in Arab countries. Dates are commonly infested with the sawtoothed grain beetle, Oryzaephilus surinamensis. Consequently, the date yield, quantity, and quality (economic value and seed viability) are negatively affected. This study was designed to investigate the effectiveness of air evacuation as eco-friendly and safe control method against adult O. surinamensis. Insects were obtained from the infested date purchased from a private store in sakaka city, Aljouf region, Saudi Arabia. Air evacuation (using a vacuum pump) and food deprivation were applied to O. surinamensis, and insect mortality was observed daily in comparison with the control group (administered both food and air). Application of both air evacuation, and food deprivation, significantly, increased the percentage of daily mortality when compared to control. Percentage accumulative mortality displayed very strong positive correlation with the time course in both cases of air-deprived and food-deprived groups. On the basis of lethal time values, the air evacuation method resulted in a comparable effect of food deprivation. Conclusively, the air-evacuation of the package is a very effective Eco-friendly and safe control method against O. surinamensis.